Reduction of urban disparities in Iraqi cities: (study in urban of geography) - Hashim Duckhle, Alaa (Al-Adab Journal, 2019)
The main objective of the study was to measure and analyze some indicators in the urban centers of Iraq, which affect the existence of disparities that lead to urban differences between these cities. Four indicators were used: the economic situation, infrastructure services, housing, and the existence of slums. According to these indicators, the infrastructure index is the most deprived of the rest of the indicators. Despite the convergence of deprivation rates in most city centers, there is a clear discrepancy between the center of the city of Maysan and the city of Dohuk, and we note the low indicator of the existence of slums except for the city of Baghdad, Basra and Nineveh, Which pointed to the existence of disparities and the existence of urban disparities between the centers of cities in southern Iraq and the northern regions as in the rise of evidence in both Maysan, while declining in Sulaymaniyah, Arbil and Anbar.